Housing co-operatives - International Labour Office (Geneva : International Labour Office, 1964)
The book is on the structure of the individual, collective ownership of housing. The management of the housing cooperatives in Scandinavian and developing countries
Includes bibliographical footnotes.
sju 25/01/2019
Loans
Keywords: Housing--cooperative.